IMPACT OF EXPULSIVE MEDICATION THERAPY ON THE PASSAGE OF URETERAL STONES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective: To assess the effectiveness of expulsive drug therapy in managing patients with ureteral stones. Materials and Methods: A total of 50 patients with ureteral calculi received a standardized regimen of expulsive medication. Results: Standard expulsive drug treatment led to spontaneous passage of ureteral stones in 40 patients (80%). Conclusions: Given its high success rate, conservative drug-based management can be considered a viable option for treating uncomplicated ureteral stones.